Pengaruh Budaya Organisasi, Gaya Kepemimpinan, Lingkungan Kerja, dan Motivasi Terhadap Kinerja Auditor Internal dalam Mencegah Kecurangan: Studi Kasus Pemerintahan Kota Balikpapan - Wianda Faza Imelba; Hairul Anam; Yanzil Azizil Yudaruddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of organizational culture, leadership style, work environment, and motivation on the performance of internal auditors at the Inspectorate of Balikpapan City in preventing fraud. Sampling technique in this research uses census method where all population members are used as respondents as many as 31 employees. Data analysis technique used in this research is validity test, reliability test, and hypothesis test using SmartPLS 3.0 application. The result of this research shows that organizational culture, leadership style, work environment, and motivation affect the performance of internal auditor at Inspectorate of Balikpapan City in preventing fraud.